Analysis of the President's Budget for 2003 - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 2002)
This study presents an evaluation of the Presidents Budget for 2003. First, it shows that the fiscal targets set out in the administrations Budget of Expenditures and Sources of Financing (BESF) for 2003 are not likely to be met. In particular, the fiscal deficit target of P130 billion (or 3.3% of GDP) for 2002 will be exceeded by P93 billion (or 2.4% of GDP). Thus, the paper projects that the national governments fiscal position will weaken from a deficit of 4.1% of GDP in 2001 to a deficit of 5.6% of GDP in 2002. In like manner, the fiscal deficit target of P142.1 billion (or 3.3% of GDP) in 2003 will also be exceeded by P34 billion P64 billion (or 0.8% - 1.5% of GDP). While the government was able to run high deficits in the last three years without hurting macroeconomic stability, danger signs have begun to emerge. On the one hand, outstanding debt of the national government has been rising rapidly, from 65.5% of GDP as of December 2001 to 68.2% as of August 2003. On the other hand, while interest rates have remained low, the yield curve on government securities is steep indicating that inflationary expectations are high. Second, the problem with the fiscal deficit stems largely from the continuous slide in tax effort. Undoubtedly, evasion continues to be a major source of the leakage in revenues and the situation appears to have worsened in 2001. However, closer analysis indicates that weaknesses in tax structure (nonindexation of excise taxes and proliferation of tax incentives) also need to be addressed. Third, in the near term, fiscal consolidation cannot be achieved unless corrections on the revenue side are effected as government expenditures have already been cut to the bone. Although the expenditure program for 2003 is P34.4 billion (or 4.5%) larger than the obligation program for the previous year, national government services in 2003 are expected to be severely constrained as non-mandatory expenditures (i.e., total national government expenditures net debt service, transfers to LGUs and pensions/retirement gratuity) are programmed to decline by 1.4% relative to the 2002 level. This means that many government agencies, including those in the social service sectors, will have to work with smaller budgets in 2003.
Keywords: 330; fiscal deficit; tax effort; fiscal sustainability; expenditure program; tax evasion; Öffentlicher Haushalt; Haushaltsdefizit; Philippinen